Changes in the epidemiological landscape of invasive candidiasis. (3rd January 2018) - Lamoth, Frederic; Lockhart, Shawn R; Berkow, Elizabeth L; Calandra, Thierry
Abstract: The epidemiology of invasive candidiasis has evolved in recent years, warranting a review of the changes and the implications for current and future diagnosis and treatment. The overall burden of invasive candidiasis remains high, particularly in the expanding populations of patients at risk of opportunistic infection, such as the elderly or immunosuppressed. Progressive shifts from Candida albicans to non- albicans Candida spp. have been observed globally. The recent emergence of novel, multiresistant species, such as Candida auris, amplifies the call for vigilance in detection and advances in treatment. Among the current treatment options, fluconazole is still widely used throughout the world. Increased resistance to fluconazole, both acquired and naturally emerging, has been observed. Resistance to echinocandins is presently low but this may change with increased use. Improvement of diagnostic techniques and strategies, development of international surveillance networks and implementation of antifungal stewardship programmes represent major challenges for a better epidemiological control of invasive candidiasis.